Numeracy literacy abilities of students with introverted personality types - Rojiyah Maghfiroh; Andika Setyo Budi Lestari; Dewi Nurmalitasari (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Numeracy literacy is the ability of students to understand, interpret, and apply mathematical concepts in various contexts of daily life. This study aims to analyze the numeracy literacy abilities of students with an introvert personality type, which has rarely been studied in previous studies. Most studies focus more on cognitive factors without considering personality, which influences students' performance in solving mathematics problems. This study involved 32 eighth-grade students of SMPN 6 Pasuruan who were classified as introverts based on Jung's Type Indicator (JTI). Data were collected through a numeracy literacy test of five questions with varying difficulty levels. The results showed that introvert students had an average score of 32.74 out of 100, with a tendency to excel in questions requiring in-depth analysis and accuracy. However, they have difficulty with tasks that require quick completion due to limitations in time management. If not addressed, this challenge can affect their academic achievement, especially in time-limited exams. Theoretically, this study enriches the understanding of numeracy literacy by considering personality factors. Practically, the results of this study can be the basis for designing more inclusive learning strategies, such as gradual training in time management. From a policy perspective, these findings provide recommendations for schools to develop more flexible assessments to support students with different learning characteristics.